A sustentabilidade nas reportagens da revista Pesquisa FAPESP: uma análise textual discursiva - Stahl, Aylon Matheus (Universidade Federal de São Carlos, 2026)
This thesis investigates how the concept of sustainability is constructed within scientific journalism and to what extent this construction aligns with the scientific concept discussed within the academic community. The study focuses on journalistic reports produced by three journalists from Revista Pesquisa Fapesp, analysed through Discursive Textual Analysis, as well as interviews conducted with these authors. The results indicate that, in the scientific journalism analysed, sustainability is predominantly associated with technology, understood as a means of increasing efficiency in the use of natural resources and as a central solution to environmental problems. This construction is strongly linked to the economic sphere, as the financial viability of technologies emerges as a relevant criterion for their legitimation as sustainable. Such a conception shows convergence with the scientific understanding disseminated by international organisations, particularly with regard to the less burdensome use of resources, while also revealing the circulation of a hegemonic view of the concept, reproduced by scientists frequently mobilised as sources. A largely unproblematised trust in science was also observed, marked by the absence of methodological discussion and by the transformation of estimates into expectations, which limits the potential for critical reflection among non-specialists. The interviews indicate that, although the journalists share elements of the scientific concept of sustainability, they also express criticism of its reduction to economic logic and the marginalisation of the social dimension. Finally, a shift was identified from a future oriented understanding of sustainability to one focused on present demands, aligned with the prevailing economic model. It is concluded that scientific journalism tends to present sustainability as a predominantly environmental and technological issue, pointing to the need to broaden the debate through practices that incorporate other actors and perspectives in the construction of this concept.
Sustainability in reports from Pesquisa FAPESP magazine: a discursive textual analysis
Keywords: Sustentabilidade; Divulgação científica; Jornalismo científico; Análise textual discursiva; OUTROS; 4. Educação de Qualidade; 13. Ação contra a Mudança Global do Clima; 16. Paz, Justiça e Instituições Eficazes